Postfeeding Larval Dispersal Behavior of Late Season Blow Flies (Calliphoridae) in Southern Ontario, Canada. Issue 5 (7th March 2014) - Turpin, Chantal; Kyle, Christopher; Beresford, David V.
Abstract Postfeeding dispersal involves migration of larvae away from their food source in order to pupate. Puparia are difficult to find, yet are important for estimating PMI, and missing puparia during collection can result in inaccurate estimations. This study investigates the late season maggot dispersal patterns for blow flies at coyote carcasses in two habitats with an aim to improving puparia collection procedures. Puparia samples collected from various dispersal distances and directions tested the spatial distribution patterns of the various species using the variance/mean ratio (VMR). Lucilia illustris was the most common species to emerge, with a preferred minimum dispersal distance of more than 50.8 cm and an overall VMR value of 14.91, indicating this species had a clumped distribution pattern. These findings highlight that current collection procedures that use random sampling from under carcasses do not adequately account for the spatial distribution of larvae.